Pancasila sebagai Sumber Hukum dalam Sistem Hukum Adat : Analisis Kesesuaian dan Tantangan Kontemporer - Ashfiya Nur Atqiya; Ahmad Muhamad Musain Nasoha; Laila Alfiani Eka Safira; Azzahra Meisya Rahmadani; Zidni Aulia Rohmah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The role of Pancasila as a source of law within the adat (customary law) system in Indonesia involves analyzing its alignment and contemporary challenges. Pancasila, as the state ideology, serves as a fundamental guide for the formulation and application of laws throughout Indonesia. However, integrating Pancasila's values into the diverse adat legal systems presents significant challenges regarding both value alignment and practical application. This study uses qualitative analysis with a case study approach to evaluate how Pancasila’s principles are implemented in adat law and assess how well these values align with existing adat norms. Findings indicate that despite efforts to reconcile Pancasila with adat law, there are several obstacles, including differences in value interpretation, resistance from indigenous communities, and difficulties in harmonizing national and adat laws. The article concludes that a more dialogic and inclusive approach is needed to align Pancasila with adat law and recommends policy reforms and enhanced understanding of Pancasila's values at the local level to ensure fair and sustainable legal enforcement.